Characterization of glycerol kinase from baker's yeast: Response surface modeling of the enzymatic reaction - Aragon, Caio Casale [UNESP]; Ferreira-Dias, Suzana; Gattas, Edwil Aparecida de Lucca [UNESP]; Sanches Peres, Maristela de Freitas [UNESP] (Elsevier B.V., 2008)
The present study describes a methodology of dosage of glycerol kinase (GK) from baker's yeast. The standardization of the activity of the glycerol kinase from baker's yeast was accomplished using the diluted enzymatic preparation containing glycerol phosphate oxidase (GPO) and glycerol kinase. The mixture was incubated at 60 degrees C by 15 min and the reaction was stopped by the SDS solution addition. A first set of experiments was carried out in order to investigate the individual effect of temperature (7), pH and substrate concentration (S), on GK activity and stability. The pH and temperature stability tests showed that the enzyme presented a high stability to pH 6.0-8.0 and the thermal stability were completely maintained up to 50 degrees C during 1 h. The K(m) of the enzyme for glycerol was calculated to be 2 mM and V(max) to be 1.15 U/mL. In addition, modeling and optimization of reaction conditions was attempted by response surface methodology (RSM). Higher activity values will be attained at temperatures between 52 and 56 degrees C, pH around 10.2-10.5 and substrate concentrations from 150 to 170 mM.This low cost method for glycerol kinase dosage in a sequence of reactions is of great importance for many industries, like food, sugar and alcohol. RSM showed to be an adequate approach for modeling the reaction and optimization of reaction conditions to maximize glycerol kinase activity. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: glycerol kinase; baker's yeast; partial purification; response surface methodology; stability